2021
DOI: 10.1007/s00586-021-07060-3
|View full text |Cite
|
Sign up to set email alerts
|

First neurological symptoms in degenerative cervical myelopathy: does it predict the outcome?

Abstract: Purpose Degenerative cervical myelopathy (DCM) is the most common non-traumatic cause of spinal cord dysfunction. Prediction of the neurological outcome after surgery is important. The aim of this study was to analyze the relationship between first symptoms of DCM and the neurological outcome after surgery. Methods A retrospective analysis over a period of 10 years was performed. First symptoms such as cervicobrachial neuralgia, sensory and motor deficits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…This design inherently introduces certain complexities, including the variability in pre-surgical JOA scores among patients. Although some studies have posited that shorter durations from symptom onset to surgery can result in better JOA improvements, our findings did not explicitly corroborate this [34,35]. Notably, in real-world clinical settings, a subset of patients often defer seeking medical attention until a significant duration has passed from symptom onset, usually when their myelopathy has considerably worsened.…”
Section: Discussioncontrasting
confidence: 59%
“…This design inherently introduces certain complexities, including the variability in pre-surgical JOA scores among patients. Although some studies have posited that shorter durations from symptom onset to surgery can result in better JOA improvements, our findings did not explicitly corroborate this [34,35]. Notably, in real-world clinical settings, a subset of patients often defer seeking medical attention until a significant duration has passed from symptom onset, usually when their myelopathy has considerably worsened.…”
Section: Discussioncontrasting
confidence: 59%
“…Importantly, the mJOA does not distinguish between unilateral and bilateral sensory loss, which could raise the risk of misclassifying radiculopathy as myelopathy, in which unilateral sensory loss is a feature. In a recent study, sensory disturbance was the presenting symptom in 19% of 411 people with DCM but it was not reported if this was bilateral or unilateral ( Özkan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…People with moderate and severe DCM will be recommended to have decompressive surgery, which has been shown to improve or stabilise neurological function, disability and quality of life ( Fehlings et al, 2017 ). Surgery is generally considered to be time-sensitive, as shorter duration of symptoms may be associated with better outcomes following surgery ( Tetreault et al, 2019 ), though the extent of this varies between studies and may depend on how outcomes are measured and analysed ( Evaniew et al, 2020 ) and which symptoms present first ( Özkan et al, 2022 ). Irrespective of a clearly-defined “window” for optimal recovery with surgery, a timely diagnosis is desirable from the point of view of understanding symptoms, monitoring change over time, and informing future management.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the most significant improvement is achieved after surgery in cases with mild-to-moderate functional involvement evaluated with the different functionality scales, compared to those with severe involvement where part of the damage could be irreversible [ 15 ]. Good postsurgical outcome is related to younger age, absence of radiographic myelopathy signs, less duration of symptoms before surgery and the presence of sensory instead of motor or gait disturbance as first symptoms [ 23 , 24 , 25 ]. The aim of our study was to correlate the clinical outcome measured by scales with the neurophysiological sensory and motor tests evolution.…”
Section: Introductionmentioning
confidence: 99%